Adam Smith’s Pragmatic Liberalism - Hill, Lisa. author. aut Link
IX, 237 p.
Keywords: Adam Smith is commonly conceived as either an economist or a moral philosopher so his importance as a political thinker has been somewhat neglected and, at times, even denied. This book reveals the integrated, deeply political project that lies at the heart of Smith’s thought, showing both the breadth and novelty of Smith’s approach to political thought. A key argument running through the book is that attempts to locate Smith on the left-right spectrum (however that was interpreted in the eighteenth century) are mistaken: his position was ultimately dictated by his social scientific and economic thought rather than by ideology or principle. Through examining Smith’s political interests and positions, this book reveals that apparent tensions in Smith's thought are generally a function of his willingness to abandon, not only proto-liberal principles, but even the principles of his own social science when the achievement of good outcomes was at stake. Despite the common perception, negative liberty was not the be-all and end-all for Smith; rather, welfare was his main concern and he should therefore be understood as a thinker just as interested in what we would now call positive liberty. The book will uniquely show that Smith’s approach was basically coherent, not muddled, ad hoc, or ‘full of slips’; in other words, that it is a system unified by his social science and his practical desire to maximise welfare. .